Social Media and its Impacts in Human Minds - Adhikari, Sulav (Unity Journal, 2022)
In today’s world, social media can make differences in the minds of people across the world. It has not only become the source of information but also is a part of human’s life. It can be termed as the vehicle of communication which lets each one of us to convey and share our content in each and every corner of the world via the internet. According to the data of the year 2020, there were more than 3.6 billion users of social media and it’s expected to increase up to 4.41 billion till 2025 which is massive. The above extracted data is huge, and it is crystal clear that social media is booming day by day. Indeed, among all the young generations are the active users of social media platforms. Knowing these data, we can observe the significance of social media in our life. The social media platforms that are utilized rapidly include Facebook, YouTube, WhatsApp, Instagram and so on. These platforms have a prominent impact on everyone’s life whether it may be positive or negative. On the one hand, the positive side includes that; it permits us to communicate and connect with our dear ones. Also, we can gain up-to-date information and news happening around the globe. Many skills and opportunities can be flourished and gained respectively with the assistance of social media and its platforms. Similarly, on the negative side, cyber bullying, fraud, rumour spreading etc. are gaining huge attention which is the drawback of social media. And mostly the youths are found being engaged in such activities. So, these social media platforms exhibit both the positive and negative sides. In summary, we observed that, if social media and its platforms are used in a productive and informative technique, then we tend to secure multiple benefits from it. Otherwise, it will take no time to degrade our valuable time and lives. After glancing, observing and analyzing the above stated statements and problem domain, discussion and explanation must be performed on how these social media and its platforms will impact and influence young high school students before their minds fully develop.